2+3−11(+3)=0
2+3−11−33=0
2−8−33=0
=−±2−4√2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c{2{\color{#c92786}{a}}}x=2a−b±b2−4ac
Приведите уравнение к общему виду, определите коэффициенты a, b и c, затем вставьте их в формулу.
x^{2}-8x-33=0x2−8x−33=0
=1
a={\color{#c92786}{1}}a=1
=−8
b={\color{#e8710a}{-8}}b=−8
=−33
c={\color{#129eaf}{-33}}c=−33
=−(−8)±(−8)2−4⋅1(−33)√2⋅1
2+3−11(+3)=0
2+3−11−33=0
2+3−11−33=0
2−8−33=0
=−±2−4√2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c{2{\color{#c92786}{a}}}x=2a−b±b2−4ac
Приведите уравнение к общему виду, определите коэффициенты a, b и c, затем вставьте их в формулу.
2−8−33=0
x^{2}-8x-33=0x2−8x−33=0
=1
a={\color{#c92786}{1}}a=1
=−8
b={\color{#e8710a}{-8}}b=−8
=−33
c={\color{#129eaf}{-33}}c=−33
=−(−8)±(−8)2−4⋅1(−33)√2⋅1